Please show the work all the way to the very answer if like terms then show the work to the very end.. thanks

## show how you arrives at the answer simplify completely 2[4(x+y) - 3(6x-15y)]

Tutors, please sign in to answer this question.

# 1 Answer

2[4(x+y) - 3(6x-15y)]

The order of operations --> PEMDAS

P = operations within Parentheses

E = Exponents

M = Multiplication

D = Division

A = Addition

S = Subtraction

First distribute the 4 across the (x+y) and the 3 across the (6x - 15y)

2[4x + 4y -18x + 45y]

Next do the addition and subtraction of like terms within the brackets [ ]

2[4x - 18x + 45y + 4y]

2[-14x + 49y]

Finally, distribute (multiply) the 2 across the terms inside the bracket and you'll have your answer.